2006
DOI: 10.1021/jp0611370
|View full text |Cite
|
Sign up to set email alerts
|

Zn Adsorption on Pd(111):  ZnO and PdZn Alloy Formation

Abstract: The adsorption and thermal desorption of Zn and ZnO on Pd(111) was studied in the temperature range between 300 and 1300 K with TDS, LEED, and CO adsorption measurements. At temperatures below 400 K, multilayer growth of Zn metal on the Pd(111) surface takes place. At a coverage of 0.75 ML of Zn, a p(2 x 2)-3Zn LEED structure is observed. Increasing the coverage to 3 ML results in a (1 x 1) LEED pattern arising from an ordered Zn multilayer on Pd(111). Thermal desorption of the Zn multilayer state leads to two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
74
3
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 42 publications
6
74
3
1
Order By: Relevance
“…Prior to catalytic measurements, the preparation of a suitable "multilayer" PdZn alloy both on the surface of Pd foil and Pd(111) was examined, building upon knowledge obtained by previous structural investigations of Zn deposition and alloy formation on Pd(111), by Bayer et al [5], Gabasch et al [6], Weirum et al [34], Kratzer et al [35] and Stadlmayr et al [12,36]. To avoid sticking coefficients of Zn smaller than 1 on the quartz microbalance, which would lead to underestimation of Zn thickness as reported in [35], the microbalance was cleaned by Ar + sputtering and cooled to below 270 K during evaporation.…”
Section: The Pdzn "Multilayer" Alloy Preparation Verified By Aes and mentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to catalytic measurements, the preparation of a suitable "multilayer" PdZn alloy both on the surface of Pd foil and Pd(111) was examined, building upon knowledge obtained by previous structural investigations of Zn deposition and alloy formation on Pd(111), by Bayer et al [5], Gabasch et al [6], Weirum et al [34], Kratzer et al [35] and Stadlmayr et al [12,36]. To avoid sticking coefficients of Zn smaller than 1 on the quartz microbalance, which would lead to underestimation of Zn thickness as reported in [35], the microbalance was cleaned by Ar + sputtering and cooled to below 270 K during evaporation.…”
Section: The Pdzn "Multilayer" Alloy Preparation Verified By Aes and mentioning
confidence: 99%
“…Related experimental studies of the Zn/Pd(111) system using XPS reported different stages of the alloying process as a function of temperature, among them the formation of the theoretically predicted 1:1 surface composition [5,11,12]. Studies performed by some of us revealed tetragonal AuCu-type PdZn nanoparticles [2] and a tetragonal PdZn nearsurface alloy formed on Pd(111) at elevated temperatures and high Zn coverages beyond 5 ML, which closely resembled the active tetragonal bulk alloy state [6]. Since the electronic structure of the 1:1 PdZn alloy is similar to that of metallic copper, a phenomenological interpretation of the observed analogous catalytic performance of both Cu and PdZn was suggested [5,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key point for understanding the catalytic pecularities of the above-mentioned Pd-Zn alloy particles is also to determine their surface composition. Recent experiments in our laboratory 33 show that a well-ordered (6x4/√3) Pd-Zn layer forms on Pd(111) under UHV conditions at elevated temperature.Preprint of the Department of Inorganic Chemistry, Fritz-Haber-Institute of the MPG (for personal use only) (www.fhi-berlin.mpg.de/ac) …”
mentioning
confidence: 90%
“…In particular, the striking differences between the Pd/SiO 2 and Pd/ZnO/SiO 2 systems demonstrated in this work may lead to a better understanding of the drastic activity and selectivity differences between Pd/SiO 2 and Pd/ZnO reported in the literature 13,23 . According to recent single crystal experiments 33,38 and theory studies 38,39 it seems that this very stable PdZn alloy phase of stoichiometric surface composition is stable over a wide range of temperatures.…”
mentioning
confidence: 99%